2016
DOI: 10.1186/s12891-016-0934-x
|View full text |Cite
|
Sign up to set email alerts
|

Modic changes in the lumbar spine and their association with body composition, fat distribution and intervertebral disc height – a 3.0 T-MRI study

Abstract: BackgroundVertebral endplate (Modic) abnormalities are important structural lesions in the spine, but their association with body composition and fat distribution have not been examined. Moreover, no study has examined whether Modic change are related to other structural features of low back pain, such as reduced intervertebral disc height.MethodsSeventy-two community-based individuals not selected for low back pain had lumbar vertebral Modic change and intervertebral disc height assessed from MRI. Dual energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Differences in the prevalence of disc degeneration and LBP symptoms between sexes have been reported [29]. Android pattern of fat distribution has been found to increase the risk of Modic change [30]. M2 may have a metabolic component in its aetiology [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the prevalence of disc degeneration and LBP symptoms between sexes have been reported [29]. Android pattern of fat distribution has been found to increase the risk of Modic change [30]. M2 may have a metabolic component in its aetiology [30].…”
Section: Discussionmentioning
confidence: 99%
“…Android pattern of fat distribution has been found to increase the risk of Modic change [30]. M2 may have a metabolic component in its aetiology [30]. Bone structure is known to depend on metabolic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Such a comparison, however, may be virtually impossible because of lumbar aging, and thus, degeneration, from the second decade of life onward [27,28]. Third, although male gender and android fat distribution have been identified as risk factors for Modic degeneration, within the study~60% of patients with Modic changes were females, which may reflect institutional MRI habits [29]. Fourth, the retrospective PLSE assessment was based on highly fluid-sensitive, sagittal STIR sequences alone, but did not include transverse T2-weighted and STIR sections with complete lumbar coverage [4,11].…”
Section: Discussionmentioning
confidence: 87%
“…In those studies where the relationship between MCs and disc degeneration has been assessed previously, MCs frequently occur at sites with degenerative disc disease. [ 29 , 30 ] In a study by Maatta et al, the authors found that disc narrowing and disc signal loss were associated with prevalent MCs, even in multivariable analysis. [ 31 ] Kerttula et al reviewed 54 patients with large MCs and concluded that MCs were associated with decrease of disc height and change in disc signal intensity.…”
Section: Discussionmentioning
confidence: 99%